London 2012 - Experience and Legacy - Nicholl, L. (8. International Forum on Elite Sport, Rio de Janeiro, Brasil, August 26, 2013 - August 31, 2013, 2013)
London 2012 Legacy - Inspiring a generation - 5 themes • Economic • Sports participation • Major Events • International Development • High Performance success